Scientific Attitudes in Scientific Online Learning Management for Student Successful Characters - Mihardi, Satria; Derlina,; Shiddiq, Hana Salsabila; Sinuraya, Jurubahasa (Advances in Social Sciences Research Journal, 2022)
The development is carried out through various studies on the perspective and interpretation of online learning. Successful education will create appropriate and decent human beings in society and will not trouble others. The learning process will be successful when students have the motivation in learning. The scientific attitude becomes a very important aspect of attitude in carrying out experiments (simple scientific activities) and becomes a benchmark when undergoing scientific activities. A scientific attitude is an attitude that is indicated by the existence of logical thinking based on facts and considered according to the basic scientific theory. This includes critical attitude, logical attitude, curious attitude, systematic, procedural, and consistency. The analysis of each indicator is the impact of learning that occurs during online learning from the recording system. The analysis was addressed to each individual of the 100 respondents. The instrument used is an observation table with a Likert scale (1 to 5). Results were shown that in various types of learning, it is necessary to optimize the delivery of material to proportionally balance each component of learning outcomes. This also requires a special assessment that is identical to several indicators of assessment from all aspects. Especially in online learning, indicator logic needs special attention and treatment to be used as a counterweight to the assessment of students' scientific attitudes. Students need to master the material logically to be able to become the basis for thinking and making decisions in acting and addressing the problems that occur.